2000
DOI: 10.1677/jme.0.0240233
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-induced expression of steroidogenic acute regulatory protein is dependent upon phosphoprotein phosphatase activities

Abstract: In addition to the well-documented role of protein kinases in the regulation of steroid production, phosphoprotein phosphatase (PP) activity is required for steroidogenesis. In the present study, we have used the mouse Y1 adrenocortical cell line to identify the site of action of PPs on steroid production by measuring the effects of PP inhibition on the expression of the steroidogenic acute regulatory (StAR) protein and on steroid production. Forskolin-induced activation of cyclic AMPdependent protein kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Our results and several previous studies (Iyer et al 1988, Sayed et al 1998, Azhar et al 1991, Jones et al 2000, Sewer & Waterman 2002 show that the activity of both serine/threonine and tyrosine phosphatases is involved in the stimulation of steroid synthesis. Since dual specificity phosphatases were described, it is possible to speculate that a phosphatase of this kind could be acting on the hormonal regulation of steroidogenesis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results and several previous studies (Iyer et al 1988, Sayed et al 1998, Azhar et al 1991, Jones et al 2000, Sewer & Waterman 2002 show that the activity of both serine/threonine and tyrosine phosphatases is involved in the stimulation of steroid synthesis. Since dual specificity phosphatases were described, it is possible to speculate that a phosphatase of this kind could be acting on the hormonal regulation of steroidogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…Given that the signaling cascade triggered by steroidogenic tropic hormones is mediated by Ser/Thr kinase activation, the studies on the role played by protein dephosphorylation were initially focused on Ser/Thr phosphatases (PPs) (Iyer et al 1988, Azhar et al 1991, Sayed et al 1998, Jones et al 2000. Several recent reports indicate that tyrosine dephosphorylation is an active component of the steroidogenic pathway (Vilgrain et at 1998, Paz et al 1999, Cornejo Maciel et al 2001, Sewer & Waterman 2002, and the present study provides evidence that PTP activity participates in the mechanism by which LH/CG and 8Br-cAMP increase StAR protein levels.…”
Section: Discussionmentioning
confidence: 68%
“…Vanadate is a well-known inhibitor for phosphoprotein phosphatase (PP) and alkaline phosphatase (ALP) (Gordon 1991) and is able to enhance the sensitivity of mouse Leydig cell proliferation in response to 17b-estradiol stimulation (Sato et al 1987). Recently, PP was reported to play a role in regulating cAMP-mediated increase in StAR protein expression and steroidogenesis in mouse Y1 adrenocortical cells (Jones et al 2000), while PPs are also involved in the elevation of mitochondria Ca 2C level that may be associated with K C -stimulated aldosterone synthesis in H295R cells (Lalevee et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that when ovarian follicles at the mid-vitellogenic stage of maturation, when the estrogenic and androgenic steroidogenic capacity of the follicle is at a maximum, are incubated in medium containing cortisol, the synthesis of 17β-estradiol (E 2 ) and testosterone (T) by the follicles is significantly suppressed [26]. However, the mechanisms and sites of action of the glucocorticoid on the steroidogenic cascade by which steroidogenesis is inhibited are currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies were undertaken to specifically examine the possible sites of inhibitory action of cortisol on four different levels of steroidogenesis, as shown in Figure 1. These were the rate-limiting step in gonadal steroidogenesis is the cAMP-regulated transfer of cholesterol (by the activation of the cholesterol transporter, steroidogenic acute regulatory (StAR) protein) from the cytosol of steroidogenic cells into the inner chamber of the mitochondria, or the expression of the gene encoding for StAR protein [26][27][28][29][30] (A), the conversion of cholesterol to pregnenolone (P5) in the inner mitochondrial chamber by the action of the enzyme, cytochrome P450 side chain cleavage (P450scc) (B), the biotransformation of progestogens to androgenic steroids by enzymes associated with the smooth endoplasmic reticulum of the thecal cells (C), and the aromatization of the androgenic steroids to estrogens by specific isoforms of cytochrome P450 aromatase (P450arom) within the granulosal cells (D).…”
Section: Introductionmentioning
confidence: 99%